(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper reports a study on the effect of phase change material (PCM) in design of cold protective clothing. Two clothing systems with the same structural design, one was smart clothing (clothing C) was treated with PCM, the other one was moisture management clothing (clothing B), were tested in a climate chamber where was controlled at -15&#176C. Eleven young male students volunteered to take part in wear trial experiments. The experimental results showed that the ear canal temperature when subjects wearing clothing treated with PCM was significantly higher that when subjects wearing moisture management clothing. The results also indicated that subjects wearing the clothing treated with PCM felt more comfortable than wearing the clothing untreated with PCM.